1968
DOI: 10.1002/jez.1401680211
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development of chick embryo explants on various protein substrates

Abstract: Chick embryo explants of 11 to 13 somites were cultured on various sources of protein in an attempt to determine if these proteins could replace the proteins of egg yolk as a nutrient substrate for the developing embryo. Various approaches were employed to provide a favorable low molecular weight supplement to the non-yolk sources of protein. After 48 hours of cultivation, the protein nitrogen and DNA contents of the embryo and the extraembryonic membrane were determined and the stages of morphological develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1971
1971
2001
2001

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In the initial experiments the procedure of Bernardi and Cook (i960) was used to separate fresh yolk into a high density and low density fraction. Employing various procedures to supply the low molecular weight supplement, as previously discussed (Klein, 1968), the high density fraction but not the low density fraction supported embryo growth and development. In fact, during 48 hours of culture embryo growth on the high density fraction was comparable to that achieved with the whole egg homogenate medium.…”
Section: Lipovitellin and Livetinmentioning
confidence: 83%
See 2 more Smart Citations
“…In the initial experiments the procedure of Bernardi and Cook (i960) was used to separate fresh yolk into a high density and low density fraction. Employing various procedures to supply the low molecular weight supplement, as previously discussed (Klein, 1968), the high density fraction but not the low density fraction supported embryo growth and development. In fact, during 48 hours of culture embryo growth on the high density fraction was comparable to that achieved with the whole egg homogenate medium.…”
Section: Lipovitellin and Livetinmentioning
confidence: 83%
“…In combination, serum and ovalbumin supported embryo growth comparable to that achieved on whole egg homogenate medium with a somewhat larger extraembryonic membrane. Klein, 1966) suggested that the active component was associated with the globulins rather than the albumins which might be expected from the observation that bovine serum albumin not only failed to support the growth of the embryo proper but the extraembryonic membrane as well (Klein, 1968).…”
Section: Nutrient Protein Complementationmentioning
confidence: 99%
See 1 more Smart Citation
“…When the growth of embryos was quantitatively evaluated, large differences were observed in the response of embryos to various protein sources (Table II) (Klein, 1968). The accumulation of protein nitrogen during a 48 hour culture period was greatest for embryos provided with whole egg homogenate medium (a mixture of yolk and white).…”
Section: A Chick Embryosmentioning
confidence: 99%
“…The first demonstration that a combination of proteins or sources of protein would support a higher level of embryo growth than could be achieved when these materials were individually provided in the medium was made with ovalbumin and serum (Klein, 1968). The combination of these two proteinaceous materials was not fortuitous but was based on the observation that serum and ovalbumin supported different parts of the chick embryo explant system.…”
Section: Nutrient Protein Complementationmentioning
confidence: 99%